A novel method and mechanism for simultaneously refining microstructure and controlling grain orientation in Ti48Al2Cr2Nb2.5C alloy. (August 2022) - Wang, Shu; Fang, Hongze; Chen, Dezhi; Chen, Ruirun; Zhou, Lingyan; Yang, Xiaokang; Su, Yanqing
Highlights: The grain size and orientation have been controlled under the coupled effect of ultrasound and arc remelting. In Ti48Al2Cr2Nb2.5C alloy, the stronger acoustic streaming effect elongates the grains and converges the refined grain orientations towards (0 0 1) in X direction of specimen primary coordinate system . This novel processing method changes the growth restriction factor and the refines the grains. Abstract: A novel method of controlling the grain size and orientation has been proposed to prepare Ti48Al2Cr2Nb2.5C alloy. Results show that the coupled effect of arc remelting and ultrasonic treatment induces three signification zones: weak/transition/strong acoustic active zones. The maximum flow rate is 0.56 m/s, and stronger acoustic streaming effect promotes a convergence of the grain orientations towards (0 0 1) in X direction of specimen primary coordinate system. Compared with the as-cast ingot, the average size of the lamellar colony decreased by 46% from 87 μm to 47 μm, after inducing the ultrasound. The substructured grains and recrystallized grains in the weak zone and strong zone are higher than that in the transition zone, however, the deformed grains in the transition zone is the highest. Arc remelting can compensate for the attenuation of the ultrasound to refine the whole ingot. The grains are refined due to high growth restriction factor with temperature gradient variation and the increase of the heterogeneous nucleation particles. This method can compensate the ultrasound attenuation and realize crystal regulation. Graphical abstract: Image, graphical abstract